2022
DOI: 10.1029/2021gl096825
|View full text |Cite
|
Sign up to set email alerts
|

Van Allen Probes Observations of Oxygen Ion Cyclotron Harmonic Waves: Statistical Study

Abstract: Although these waves are generally referred to as fast magnetosonic waves or equatorial noise in the literature, linear dispersion theory and kinetic simulations suggest that these waves are essentially proton Bernstein waves generated through the proton Bernstein instability driven by a ring-like proton velocity distribution, f p , with a positive slope ∂f p (v ⊥ )/∂v ⊥ > 0 (L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…Since bicoherence (or bispectral) analysis is a very useful diagnostic tool to discriminate between nonlinearly coupled waves and spontaneously excited waves (Kim & Powers, 1979), it is important to perform bicoherence analysis for the OCH waves found in Wang et al. (2022) to check whether any of the waves have been identified incorrectly.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since bicoherence (or bispectral) analysis is a very useful diagnostic tool to discriminate between nonlinearly coupled waves and spontaneously excited waves (Kim & Powers, 1979), it is important to perform bicoherence analysis for the OCH waves found in Wang et al. (2022) to check whether any of the waves have been identified incorrectly.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen ion cyclotron harmonic (OCH) waves have been observed in the terrestrial magnetosphere with discrete multiple spectral peaks near the harmonics of the local oxygen ion cyclotron frequency (H. Liu et al., 1994; Min et al., 2017; Usanova et al., 2016; Wang et al., 2022; Yu et al., 2017). The observed waves are transverse and electromagnetic, have mixed left‐hand and right‐hand polarization, and propagate almost parallel to the background magnetic field, as derived using the singular value decomposition (SVD) method (Santolík et al., 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These waves were observed by the Akebono satellite inside the plasmasphere ( L = 1.5–2.5) (H. Liu et al., 1994), by Van Allen Probes outside the plasmasphere (Usanova et al., 2016; Yu et al., 2017), and by the Magnetospheric Multiscale (MMS) mission inside the plasma sheet boundary layer (Usanova et al., 2018). A statistical study based on Van Allen Probes showed that OCH waves occur over a wide L range (2 < L < 6) and across all magnetic local times, and more than 50% of the events are observed just outside the plasmapause (Wang et al., 2022). They occur near the magnetic equator during geomagnetic storms with oblique wave normal angles (WNAs) (H. Liu et al., 1994; Yu et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These waves were observed by the Akebono satellite inside the plasmasphere (L = 1.5-2.5) (H. Liu et al, 1994), by Van Allen Probes outside the plasmasphere (Usanova et al, 2016;Yu et al, 2017), and by the Magnetospheric Multiscale (MMS) mission inside the plasma sheet boundary layer (Usanova et al, 2018). A statistical study based on Van Allen Probes showed that OCH waves occur over a wide L range (2 < L < 6) and across all magnetic local times, and more than 50% of the events are observed just outside the plasmapause (Wang et al, 2022). They occur near the magnetic equator during geomagnetic storms with oblique wave normal angles (WNAs) (H. Liu et al, 1994;Yu et al, 2017).For those oblique OCH waves, Pokhotelov et al (1997) used an analytical model to explain that the free energy can be provided by the loss cone or ring-like distributions of hot oxygen ions, which provide a positive slope along the perpendicular direction in the oxygen ion phase space density (∂f/∂v ⊥ > 0) to excite oxygen ion Bernstein mode (OIBM) waves, and such distributions occur during geomagnetically active times (Kronberg et al, 2012).…”
mentioning
confidence: 99%